Adaptive discrete-smeared crack (A-DiSC) model for multi-scale progressive damage in composites. (October 2019) - Lu, X.; Ridha, M.; Tan, V.B.C.; Tay, T.E.
Abstract: Apart from major cracks and delamination, extensive and diffused short matrix micro-cracks are generally observed in composite laminates. In principle, discrete crack models (DCM) offer greatest fidelity to the mechanics of crack growth, including interactions between different failure modes, but it is impractical to model numerous cracks explicitly beyond coupon-sized laminates. Smeared crack models (SCM), on the other hand, treat diffused damage by effective material degradation. However, homogenization of cracks does not model strong discontinuities and delamination-matrix crack interactions. An adaptive discrete-smeared crack model is proposed here to preserve fidelity to the fracturing process while maintaining efficiency and simplicity in modelling distributed damage. DCM is used to model individual matrix cracks at the initial stages of propagation. Subsequently, adaptive transition from DCM to coupled DCM/SCM is performed. Critical cracks are explicitly retained, while non-critical ones are modelled by dispersed damage. The method is demonstrated with off-axis and open-hole tension tests.